A Transformative Subfield in Rehabilitation Science at the Nexus of New Technologies, Aging, and Disability - Winstein, Carolee J.; Requejo, Philip S.; Zelinski, Elizabeth M.; Mulroy, Sara J.; Crimmins, Eileen M. (Frontiers in Psychology, 2012)
We argue that a silo research and training approach is no longer sufficient to provide real solutions to the complex humanitarian, social, and financial problems brought about by global trends in aging and the increased prevalence of multiple chronic conditions that limit independence and activities of daily living. This perspective highlights the opportunities for collaborative research and training in a new multidisciplinary science of rehabilitation enabled by growing knowledge and information along scientifically and clinically meaningful lines. The recent proliferation of eHealth technologies offers opportunities for development of low-cost, simple, interactive media prevention, health maintenance, and continued functional recovery programs using a chronic care model designed to promote engagement and participation. With two examples—long-term disability consequential to 1) hip fracture and 2) manual wheelchair use—we outline the developing science for a collaborative and transformative nexus team capable of accelerating an understanding of ways to restore independence and improve quality of life, in the long term. We conclude with a set of recommendations for the design of interactive media systems to both increase acceptabi